Damage control in elective surgery. Does it make sense? About a clinical case - Valente, Pedro (2013)
Damage control surgery is one of the major advances in surgical technique in the past 20 years. The concept has developed in the trauma surgery context. It consists on the management of unstable patients in a fast, efficient and provisional way. The objective is an haemorrhage control, limiting contamination, and temporary closure of the abdomen. The defi- nitive repair is performed after patient stabilization. Recently, the concept of damage control surgery has been extended beyond the trauma context. There are few and only non randomi- zed studies about that, but it is the beginning of a new concept in surgical rationale. Using a clinical case report, the authors show that major surgery can be complicated with metabolic and hemodynamic failure of the patient, and because it is associated with high mortality rates, the surgeon must need to understand and use the concept of damage control approach in elective surgery, always associated with good surgical sense. Keywords: Damage control surgery, Abbreviated laparotomy, Elective surgery, Trauma, Lethal triad. Surgical complications